Félix Hedde (1879-1960) - Bùi Thiện Thảo, Jérôme (Revue des sciences philosophiques et théologiques, 2018)
Bishop Felix Hedde (1879-1960), O.P., was a key figure in the mission of the Dominicans of Lyon in Upper Tonkin. His long ministry in Viet Nam (1926-1960) made him a privileged witness to a dramatic period in the country's history. He experienced the prosperous years of French colonization until 1940, the sufferings of his compatriots during the Second World War and the Indochina War, their humiliation in the face of forced decolonization, and finally the open and covert persecution of Christians under the communist regime. In Felix Hedde we find a love for Tonkin's mission and a desire to implant the Church there, in combination with a desire to honor his familial and national traditions. The ordeal of the Japanese occupation, the Indochina war, the defeats of the French army, as well as the encouragement of the fidelity of the Vietnamese Christians of the mission in an increasingly critical situation, freeing Bishop Hedde of his patriotic dreams, led him to fulfill his missionary vocation. Nonetheless, the particular conditions of his mission territory, where the Montagnards are very much in the majority, led him to propose as his successor the Frenchman André Jacq, thus depriving the local Christians of a bishop from 1958 to 1990.